Effect of core stabilization exercises on cervical sagittal balance parameters in patients with forward head posture: a randomized controlled trial in Egypt - Ahmed Mahmoud Mohamed Shabana; Abeer Farag Hanafy; Ahmad Salamah Yamany; Reda Sayed Ashour (Asian Spine Journal)
Study Design A randomized controlled trial using a pretest-posttest control group design. Purpose This study investigated the effects of core stabilization exercises (CSEs) on cervical sagittal vertical alignment (cSVA), Cobb’s angle, and Neck Disability Index (NDI) scores in patients with forward head posture (FHP). Overview of Literature FHP is a local poor neck posture. However, it is frequently caused by sagittal lumbopelvic malalignment. Therefore, an alternative view by which we can begin proximal neuromuscular control is necessary. Methods This study included 36 patients with FHP with a mean age of 27±2.63 years. These patients were randomly assigned to the two following groups: experimental group A (n=19), which received CSEs and postural correctional exercises (PCEs), , and control group B (n=17), which received only the PCE program. Randomization was performed using the computer-generated block randomization method. Training was applied 3 times per week and lasted for 6 weeks. Data were collected before and after training using lateral view cervical X-ray and NDI. Results Two-way mixed-design multivariate analysis of variance revealed significant improvements in mean cSVA and NDI values after training (p<0.05) in experimental group (A) compared with pre-training values, whereas no significant differences in these values were observed after training in the control group. In contrast, no significant difference in the mean Cobb angle values after training was observed between the groups. Conclusions Adding CSEs to PCEs is more effective than performing PCEs alone for managing FHP. The trial was registered in the ClinicalTrials.gov registry under the registration number NCT06160245.